2016
DOI: 10.12659/msm.898015
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin A Ameliorates Myocardial Ischemia-Reperfusion Injury in Mice by Suppression of Microvascular Thrombosis

Abstract: BackgroundThe aim of this study was to evaluate the cardio-protective roles of glaucocalyxin A (GLA) in myocardial ischemia-reperfusion injury and to explore the underlying mechanism.Material/MethodsMyocardial ischemia-reperfusion in wild-type C57BL/6J mice was induced by transient ligation of the left anterior descending artery. GLA or vehicle (solvent) was administrated intraperitoneally to the mice before reperfusion started. After 24 h of myocardial reperfusion, ischemic size was revealed by Evans blue/TTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…GLA administration significantly reduces infarct size, improves left ventricular ejection fraction, and left ventricular fractional shortening in mice subjected to myocardial I/R. The protective effect of GLA myocardial I/R injury is proposed to be mediated by the attenuation of microvascular thrombosis 15 . Based on the mechanism investigations, increased production of ROS and ROS-mediated oxidative damage during the I/R process play crucial roles in the development of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLA administration significantly reduces infarct size, improves left ventricular ejection fraction, and left ventricular fractional shortening in mice subjected to myocardial I/R. The protective effect of GLA myocardial I/R injury is proposed to be mediated by the attenuation of microvascular thrombosis 15 . Based on the mechanism investigations, increased production of ROS and ROS-mediated oxidative damage during the I/R process play crucial roles in the development of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GLA might be an attractive candidate for improving the prognosis of acute MI by controlling cardiac fibrosis 14 . Additionally, GLA was reported to ameliorate myocardial I/R injury in mice through the attenuation of microvascular thrombosis 15 . However, the effects of GLA on I/R-mediated oxidative stress and apoptosis in cardiomyocytes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Creatine kinase, which located in mitochondria and plasma of tissues including brain tissue, skeletal muscle, and cardiac muscle, is a key kinase correlated with ATP regeneration, intracellular energy transportation and muscle contraction and is widely utilized as a biomarker of myocardial injury [29]. Additionally, an experiment presented that LVEF and LVFS in mice with myocardial I/R injury was improved by treatment [30]. A study revealed that myocardial I/R insult declined LVEF and + dp/dtmax, increased LVEDP, serum CK, LDH, and cTnT levels, also reduced SOD activity and raised MDA level in the myocardial tissue [31].…”
Section: Discussionmentioning
confidence: 99%
“…Tumour necrosis factor-α, IL-6, and IL-1β are well-known pro-inflammatory cytokines that are involved in inflammatory responses. 11,13 The results of enzyme-linked immunosorbent assay (ELISA) showed that treatment with H 2 O 2 markedly induced the production of TNFα, IL-6, and IL-1β in HCASMCs; however, this effect was reversed by GLA pretreatment in a dose-dependent manner (Figure 4).…”
Section: Glaucocalyxin a Decreases The Production Of Tumour Necrosimentioning
confidence: 99%
“…Glaucocalyxin A (GLA), an active ent‐kauranoid diterpenoid isolated from Rabdosia japonica var. glaucocalyx , was reported to possess anti‐inflammatory, anti‐tumour, anti‐fibrotic, and cardioprotective activities . In addition, Li et al reported that GLA significantly inhibited platelet activation and thrombus formation.…”
Section: Introductionmentioning
confidence: 99%